Gastric schwannoma: An important differential for gastric submucosal tumors - A rare case report - Pardasani, Madhur; Mittal, Amol; Baral, Sonia; Thakur, Sanjiv (Indian Journal of Case Reports, 2018)
Schwannomas are slow-growing asymptomatic neoplasms that rarely occur in the gastrointestinal (GI) tract. It is a submucosal tumor arising in the neural plexus of the stomach. We herein describe the case of a 60-year-old male who presented with dull aching abdominal pain associated with nausea. While general examination appeared normal, imaging showed a well-defined isodense lesion in the anterior wall of stomach suggestive of leiomyoma. Upper GI endoscopy revealed a globular mass highly suspicious of gastric malignancy. Laparoscopic wedge resection was carried out. Very frequently misdiagnosed as gastrointestinal stromal tumors; hence, it is essential to differentiate schwannomas from mesenchymal tumors.